Derivative state constrained optimal H2 integral servo controller with a prescribed degree of stability - Komine, Noriyuki; Benjanarasuth, Taworn; Ngamwiwit, Jongkol (My University, 2005)
In this paper, the derivative state constrained optimal H2 integral servo controller is presented based on the optimal H2 control problem with a prescribed degree of stability to reduce under damped responses of the controlled linear systems. The proposed servo controller stabilizes the controlled system with a prescribed degree of stability such that its output tracks a step reference input in an optimal H2 control sense. It is shown that the derivative state constrained optimal H2 integral servo problems with a prescribed degree of stability can be reduced to the standard optimal H2 control problem. The application of the proposed method is illustrated by a simulation example of the crane model system to show its effectiveness. ©2005 IEEE.
Keywords: Derivative state constraints; Optimal H2 integral servo problem; Prescribed degree of stability